An anatomical hypothesis: a "concentric-structured model" for the theoretical understanding of the surgical anatomy in the upper mediastinum required for esophagectomy with radical mediastinal lymph node dissection. Issue 8 (17th December 2018) - Fujiwara, H; Kanamori, J; Nakajima, Y; Kawano, T; Miura, A; Fujita, T; Akita, K; Daiko, H
SUMMARY: Understanding the surgical anatomy is the key to reducing surgical invasiveness especially in the upper mediastinal dissection for esophageal cancer, which is supposed to have a significant impact on curability and morbidity. However, there is no theoretical recognition regarding the surgical anatomy required for esophagectomy, although the surgical anatomy in abdominal digestive surgery has been developed on the basis of embryological findings of intestinal rotation and fusion fascia. Therefore, we developed a hypothesis of a 'concentric-structured model' of the surgical anatomy in the upper mediastinum based on human embryonic development. This model was characterized by three factors: (1) a concentric and symmetric three-layer structure, (2) bilateral vascular distribution, and (3) an 'inter-layer potential space' composed of loose connective tissue. The concentric three-layer structure consists of the 'visceral layer', the 'vascular layer', and the 'parietal layer': the visceral layer containing the esophagus, trachea, and recurrent laryngeal nerves as the central core, the vascular layer of major blood vessels surrounding the visceral core to maintain the circulation, and the parietal layer as the outer frame of the body. The bilateral vascular distribution consists of the inferior thyroid arteries and bronchial arteries originating from the bilateral dorsal aortae in an embryo. This bilateral vascular distribution may be related to the formation of the proper mesentery of the esophagus and frequent lymph node metastasis observed in the visceral layer around recurrent laryngeal nerves. The three concentric layers are bordered by loose connective tissue called the 'inter-layer potential space'. This inter-layer potential space is the fundamental factor of our concentric-structured model as the appropriate surgical plane of dissection. The peripheral blood vessels, nerves, and lymphatics transition between each layer, thereby penetrating this loose connective tissue forming the inter-layer potential space. Recurrent laryngeal nerves also transition from the vascular layer after branching off from the vagal nerves and then ascend consistently in the visceral layer. We investigated the validity of this concentric-structured model, confirming the intraoperative images and the surgical outcomes of thoracoscopic esophagectomy in a prone position (TSEP) before and after the introduction of this hypothetical anatomy model. A total of 226 patients with esophageal cancer underwent TSEP from January 2015 to December 2016. After the introduction of this model, the surgical outcomes in 105 patients clearly improved for the operation time of the thoracoscopic procedure (160 min vs. 182 min, P  = 0.01) and the incidence of recurrent laryngeal nerve palsy (19.0% vs. 36.4%, P  = 0.004). Moreover, we were able to identify the concentric and symmetric layer structure through surgical dissection along the inter-layer potential space between the visceral and vascular layers ('viscero-vascular space') in all 105 cases after introduction of the hypothetical model. The concentric-structured model based on embryonic development is clinically beneficial for achieving less-invasive esophagectomy by ensuring a theoretical understanding of the surgical anatomy in the upper mediastinum.